2008
DOI: 10.1159/000129650
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Supplements in Cystic Fibrosis Patients

Abstract: Aim: To study the effect of Zn supplements in cystic fibrosis (CF) on disease evolution. Methods: A retrospective study of all CF patients treated with Zn supplements (January 2002 to December 2004). Data from patient files for the year before and the first year of supplementation were compared. The controls were CF patients with normal serum Zn and without Zn supplementation. Results: 21 patients (7 females), median age 8.9 (interquartile range 13.1) years, received 5 mg/kg Zn sulfate/day (maximum 150 mg). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 50 publications
1
31
0
5
Order By: Relevance
“…Growth faltering observed in older children with cystic fibrosis (CF) is undoubtedly multifactorial, including malnutrition, but in one report, older children's total zinc intake and zinc status were adequate and unrelated to growth status [50]. In contrast, in another retrospective chart review, high-dose (5 mg zinc/kg/day) supplementation was associated with beneficial effects on growth and pulmonary function [51]. However, no controlled trials are available that replicate these effects.…”
Section: Acquired Zinc Deficiencymentioning
confidence: 99%
“…Growth faltering observed in older children with cystic fibrosis (CF) is undoubtedly multifactorial, including malnutrition, but in one report, older children's total zinc intake and zinc status were adequate and unrelated to growth status [50]. In contrast, in another retrospective chart review, high-dose (5 mg zinc/kg/day) supplementation was associated with beneficial effects on growth and pulmonary function [51]. However, no controlled trials are available that replicate these effects.…”
Section: Acquired Zinc Deficiencymentioning
confidence: 99%
“…Reduced levels of plasma interleukin-6 and interleukin-8 were also documented. 7 In a retrospective review of 21 subjects, Van Biervliet et al 6 reported a decrease in pulmonary exacerbations, from 3 to 2 (P Ͻ .02), as well as an increase in the FEV 1 from 72.0 to 76.5% (P Ͻ .02). They also observed an improvement in weight for height, from 90 to 94% (P ϭ .043).…”
Section: Discussionmentioning
confidence: 98%
“…18,19 Data on zinc supplementation among children with cystic fibrosis are limited to 4 studies. [6][7][8][9] Safai-Kutti et al, 9 in their placebo-controlled double-blind crossover study in children with cystic fibrosis (N ϭ 13, age 2 y, 3 months to 19 y, 1 month), gave zinc supplementation and placebo to the subjects for 6 months. They observed that all subjects had low plasma zinc levels at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations